Analisis Kinerja Portofolio Saham LQ45 Sebelum dan Sesudah Pandemi COVID-19 di Bursa Efek Indonesia - Juliyana Puspita Sari; Delvi Mayang Sari; Bayu Riski Saputra (Journal Of Business, Finance, and Economics (JBFE), 2026)
This study aims to analyze differences in the portfolio performance of LQ45 stocks on the Indonesia Stock Exchange before and after the COVID-19 pandemic. Portfolio performance was measured using Sharpe Ratio, Treynor Ratio, and Jensen Alpha methods during the pre-pandemic period (January 2019–February 2020) and post-pandemic period (March 2020–December 2021). The research sample consisted of stocks consistently listed in the LQ45 index throughout the research period using purposive sampling, resulting in 30 companies. Secondary data comprising daily stock prices were obtained from the official Indonesia Stock Exchange website and Yahoo Finance. The Kolmogorov-Smirnov test was employed for normality testing, and hypothesis testing used the Paired Sample T-Test or Wilcoxon Signed Rank Test. The results indicate a significant difference in LQ45 stock portfolio performance before and after the COVID-19 pandemic across all three measurement methods. Portfolio performance declined drastically in the early pandemic period (March–April 2020), but gradually recovered by the end of the post-pandemic period. This study provides implications for investors in adjusting their investment strategies to face global economic crisis conditions.